2018
DOI: 10.1186/s12711-018-0421-y
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of selection and environmental adaptation across the goat genome post-domestication

Abstract: BackgroundSince goat was domesticated 10,000 years ago, many factors have contributed to the differentiation of goat breeds and these are classified mainly into two types: (i) adaptation to different breeding systems and/or purposes and (ii) adaptation to different environments. As a result, approximately 600 goat breeds have developed worldwide; they differ considerably from one another in terms of phenotypic characteristics and are adapted to a wide range of climatic conditions. In this work, we analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 111 publications
6
125
0
2
Order By: Relevance
“…CUX1 controls hair coat phenotypes in mice 87 . Alleles within CUX1 can be used to differentiate between breeds of goats raised for meat versus those raised for fiber 88 . The role of CUX1 in hair coat phenotypes makes it a prime adaptive candidate in environments where animals are under heat, cold, or toxic fescue stress.…”
Section: Envgwas Detects Allele Frequency Differences Between Discretmentioning
confidence: 99%
“…CUX1 controls hair coat phenotypes in mice 87 . Alleles within CUX1 can be used to differentiate between breeds of goats raised for meat versus those raised for fiber 88 . The role of CUX1 in hair coat phenotypes makes it a prime adaptive candidate in environments where animals are under heat, cold, or toxic fescue stress.…”
Section: Envgwas Detects Allele Frequency Differences Between Discretmentioning
confidence: 99%
“…In the current study, we confirmed three selection signatures detected by Bertolini et al . () and found two new selection signatures never detected before. The very well‐known genes involved in coat color determination, ADAMTS20 on chromosome 5 and ASIP on chromosome 13, had already been found in several groups of breeds: for the ADAMTS20 gene, the southwestern European group (which includes the Pyrénées population; the Argentata dell'Etna breed from the southeastern European group; and the Sahel, Peuhl and Targi breeds from northwestern Africa) and for the ASIP gene, the Kacchan population from the Pakistani breeds and the Alpine, Poitevine and Valdostana breeds from the Alpine group.…”
Section: Discussionmentioning
confidence: 75%
“…Blood samples of forty eight female GRF goats were collected and animals were genotyped with the Illumina GoatSNP50 BeadChip (Illumina Inc., San Diego, CA) containing 53,347 Single Nucleotide Polymorpishms (SNPs) [12]. Genomic data of nine Italian autochthonous goat breeds, namely Argentata dell’Etna (ARG), Bionda dell’Adamello (BIO), Ciociara Grigia (CCG), Di Teramo (DIT), Garganica (GAR), Girgentana (GGT), Orobica (ORO), Valdostana (VAL) and Valpassiria (VSS) were downloaded from the online repository (https://datadryad.org/stash/dataset/doi:10.5061/dryad.v8g21pt10.5061/dryad.v8g21pt) of the ADAPTmap project [3,13]. The breeds were selected based on the breed abbreviation on the plink fam file downloaded from the repository and the breed description (code and country) reported in Table 1 of [13].…”
Section: Methodsmentioning
confidence: 99%
“…Genomic data of nine Italian autochthonous goat breeds, namely Argentata dell’Etna (ARG), Bionda dell’Adamello (BIO), Ciociara Grigia (CCG), Di Teramo (DIT), Garganica (GAR), Girgentana (GGT), Orobica (ORO), Valdostana (VAL) and Valpassiria (VSS) were downloaded from the online repository (https://datadryad.org/stash/dataset/doi:10.5061/dryad.v8g21pt10.5061/dryad.v8g21pt) of the ADAPTmap project [3,13]. The breeds were selected based on the breed abbreviation on the plink fam file downloaded from the repository and the breed description (code and country) reported in Table 1 of [13]. The two datasets were merged and quality control was conducted in PLINK v1.9 [3, 4] on the final dataset based on the following criteria: 1) only autosomes were kept, ii) call rate per SNP >95% and ii) missing values per sample <10%.…”
Section: Methodsmentioning
confidence: 99%